4=5(-4n+3)

Simple and best practice solution for 4=5(-4n+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4=5(-4n+3) equation:



4=5(-4n+3)
We move all terms to the left:
4-(5(-4n+3))=0
We calculate terms in parentheses: -(5(-4n+3)), so:
5(-4n+3)
We multiply parentheses
-20n+15
Back to the equation:
-(-20n+15)
We get rid of parentheses
20n-15+4=0
We add all the numbers together, and all the variables
20n-11=0
We move all terms containing n to the left, all other terms to the right
20n=11
n=11/20
n=11/20

See similar equations:

| 4(w+6)=-36 | | -3=y/2-1 | | 6d+7=-3 | | x+x5=16 | | 56=16v-8v | | 0=3x^2-18x-6 | | g-(-3)=-7 | | 175m-125m+38.200=40.000-150m | | 14-z-5=5z+3 | | 18=4-2f | | a-199=-16a-15 | | -8+8m+5=-6+8m | | 1c+1c=18 | | 180=x+9+x-2+5x-11 | | -5-4r=-5r | | x+9=x-2+5x-11 | | 18=1c+1c | | x+90=11x | | 9j-3=9j | | 4x-12=8x-92 | | 6a+1a=140 | | 4x+45=x+78 | | 9+9p=9p+9 | | 4x-44=x+13 | | x-8x4/5=20 | | 3x-61=x-9 | | 9y-1y=-48 | | -9g+10=-10-7g+2 | | -3(2x-4)=4x-8 | | 3n-4=-6n-4 | | 3s=7+3s | | -3q=-2q+6 |

Equations solver categories